The «African Mirage» is a delusion indeed. The distribution of the obsidian from Pantelleria rejects a Maghreb route for the neolithization of Iberia - Zilhão, João (2015)
The hypothesis of a North African route for the spread of farming economies into southern and western Iberia presupposes an earlier emergence of the Neolithic in the Maghreb, where it would have emerged through cultural diffusion from Sicily. These premises are not supported by the archeological evidence. In North Africa, the earliest directly dated domesticates post‑date by several centuries similar evidence from Valencia, Andalucía and Portugal. The finding in the nearest mainlands of obsidian from the island of Pantelleria, located about half‑way between Tunisia and Sicily, substantiates prehistoric navigation between Europe and Africa in the central Mediterranean but not before ~5000 cal BC, when farming economies were already several centuries old in Iberia. The material culture similarities perceived in the Early Neolithic of southern Iberia and the Maghreb may indicate a North‑to‑South diffusion of farming across the Strait of Gibraltar but not the reverse.